Association between physical capacity and occupational falls among middle‐aged and older farmers in Thailand: Using the self‐check risk assessment tool in Japan. Issue 1 (3rd November 2021) - Arphorn, Sara; Lertvarayut, Teepapipat; Kiatkitroj, Kanpitcha; Theppitak, Chalermsiri; Manothum, Aniruth; Hara, Kunio; Ishimaru, Tomohiro
Abstract: Objectives: Declining physical capacity caused by aging increases the risk of occupational falls on the same level and to lower levels. In emerging countries in Asia, the development of a program for older farmers to assess their risk of occupational falls is valuable. The current study aimed to evaluate the relationship between physical capacity and experience of occupational falls among middle‐aged and older Thai farmers. Methods: We conducted a cross‐sectional survey of 419 Thai farmers aged 40 years and over during March and April, 2021. For the assessment of physical capacity, we used the Self‐Check Risk Assessment of Falls and Other Accidents in the Workplace tool developed in Japan, consisting of five physical test components. Multiple logistic regression and receiver operating characteristic curves were used to analyze the data. Results: The results revealed that 25.5% of participants had experienced occupational falls in the past 12 months. For each of the five physical test components, there was no significant association between physical capacity and experience of occupational falls. The area under the receiver operating characteristic curve was less than 0.60 for each of the five physical test components. A similar trend was observed when the analysis was limited to participants aged 50 years and over. Conclusions: The current study did not reveal any associations between physical capacity in each test and experience of occupational falls among middle‐aged and older Thai farmers. Because the mechanisms underlying occupational falls are complex, multiple intervention approaches may be important for preventing accidents.